A clockless method of flicker noise suppression in continuous-time acquisition of biosignals - Maslik,M; Lande,TS; Constandinou,TG (IEEE, 2018)
This paper presents a novel chopping method allow-ing suppression of 1/f flicker noise in continuous-time acquisitionsystems without the need for a fixed-frequency clock, stochasti-cally deriving the chopping signal from the input and henceachieving completely signal-dependent power consumption. Themethod is analysed, its basis of operation explained and a proof-of-concept implementation presented alongside simulated resultsdemonstrating an increase in achieved SNR of more than 8 dBduring acquisition of ECG, EAP and EEG signals.